K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 5 2019

\(2n-3⋮n-1\)

\(\Rightarrow2n-3+n-1⋮n-1\)

\(\Rightarrow2n-3+2\left(n-1\right)⋮n-1\)

\(\Rightarrow2n-3+2n-2⋮n-1\)

\(\Rightarrow1⋮n-1\)

\(\Rightarrow n-1\inƯ\left(1\right)=1\)

\(\Rightarrow n=2\)

3 tháng 5 2019

2n+3=2n+2+1=2(n+1)+1

để 2n+3 \(⋮\)n+1 thì 2(n+1)+1 \(⋮\)n+1

Mà 2(n+1) \(⋮\)n+1=> 1 \(⋮\)n+1

=> n+1\(\in\)Ư(1)={1;-1}

. Nếu n+1=1=> n=0

.Nếu n+1 =-1=> n=-2

vậy nếu n=0 hoặc n=-2 thì 2n-3 chia hết cho n+1